2013
DOI: 10.1177/1049909113515068
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in HIV-Positive Patient and Health Care Provider Perspectives on Death, Dying, and End-of-Life Care

Abstract: The purpose of this study was to investigate how HIV-positive patients and infectious disease healthcare providers think about death, dying, and end-of-life care planning. We conducted separate in-depth qualitative interviews with 47 patients and 11 providers. Interview data were transcribed and analyzed using a secondary comparative method. Patients and providers demonstrated profound differences in their perspectives on patient empowerment and attributions of control related to disease progression, imminence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Findings by Mosack and Wandrey and others suggest that PLHIV look to their healthcare providers for education on healthcare planning, including but not limited to treatment regimens, preventive care, and ACP information [27][28][29][30]. Other studies suggest that clinicians often avoid discussion of ACP and end-of-life care entirely, due to lack of training in how to counsel patients [28,29].…”
Section: Healthcare Engagement and Acpmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings by Mosack and Wandrey and others suggest that PLHIV look to their healthcare providers for education on healthcare planning, including but not limited to treatment regimens, preventive care, and ACP information [27][28][29][30]. Other studies suggest that clinicians often avoid discussion of ACP and end-of-life care entirely, due to lack of training in how to counsel patients [28,29].…”
Section: Healthcare Engagement and Acpmentioning
confidence: 99%
“…Other studies suggest that clinicians often avoid discussion of ACP and end-of-life care entirely, due to lack of training in how to counsel patients [28,29]. Furthermore, beyond discussion of these factors, rapport and trust in healthcare providers may be crucial to patients' engagement in care and willingness to discuss and/or document ACP [27][28][29][30]. Research to explore the interaction of patients, informal caregivers, and ACP discussion with healthcare providers is currently understudied among PLHIV, particularly those who inject drugs.…”
Section: Healthcare Engagement and Acpmentioning
confidence: 99%
See 1 more Smart Citation
“…These deaths are geographically clustered in southern states (CDC, 2014; Reif et al, 2014; Reif & McAllester, 2015). Treatment failure and loss of decision-making capacity through HIV Associated Neurological Disease (Allison, Wolters, & Brouwers, 2009) also make early pACP critical in this already disadvantaged population (Mosack & Wandrey, 2015; Selwyn & Forstein, 2003). Thus, despite the currently available chronic treatment options and improved life expectancy, complications can arise at any time, especially for those with perinatally acquired HIV who were born at a time when current treatments were not available, and who may have suffered critical medical events at a young age that may have latent health effects emerge as they age into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among African-Americans, advance directive completion was significantly greater for participants in FACE ACP than HLC. The FACE trial overcame previously identified barriers to ACP completion and documentation for PLWHs 35,36 and ethnic/racial minorities. 37e41 Furthermore, approximately 40% of this sample of PLWHs reported incomes below the federal poverty level and a high school education or less, suggesting this model also overcame socioeconomic barriers to ACP completion found in previous studies.…”
Section: Discussionmentioning
confidence: 99%